Gender congruence and entrepreneurial investments: the role of others’ reactions - Wieland, Alice (International Journal of Gender and Entrepreneurship, 2025)
The purpose of this research is to explore the decision processes that underlie the gender gap in entrepreneurial investments. The present research explores how gender congruence with a sex-typed business opportunity influences anticipated reactions from others who may provide or withhold support and resources, how these affect the assessed probability of venture success and the amount the entrepreneur is willing to invest (WTI) in the opportunity.,A theoretical model is presented and empirically tested via path analysis. A pilot and an experimental study model explore how gender congruence influences entrepreneurial investment decisions. The experimental study uses a repeated measures design examining the experimental effects two sex-typed business opportunities crossed with participant gender (gender congruence) on anticipated others’ reactions, assessed probability of venture success and investment amount (WTI).,Gender congruence of a business opportunity influences anticipated others’ reactions, whether they will be supportive or not, of pursuing the opportunity. This in turn influences the estimated probability of success of the venture and the amount the prospective entrepreneur is willing to invest in it. These socio-cognitive decision processes reinforce the gender gap in entrepreneurship since participants anticipate less access to others’ support for gender incongruent opportunities. Although the mediational model indicates most proposed relationships and paths are invariant across genders, the exception was that women did not report higher WTI for the gender congruent venture.,The research applies the latest thinking in social psychology on gender norm violations to entrepreneurship, measuring how anticipated reactions from others are a factor in predicting estimates of venture success probability and self-investments.
Keywords: dept.mgt; peer-reviewed

The interplay of power, incentives, academic freedom, and gender equity - Wieland, Alice; Jansen, Amy (Journal of Academic Freedom, 2024)
Alice Wieland and Amy Jansen explore the intersection of how power, adverse incentives, and gender bias combine to perpetuate gender inequity in higher education.
Keywords: dept.lib; dept.mgt

Gendered cognitions: a socio-cognitive model of how gender affects entrepreneurial preferences - Wieland, Alice M.; Kemmelmeier, Markus; Gupta, Vishal K.; McKelvey, William (Understanding Women's Entrepreneurship in a Gendered Context, 2021)
Keywords: dept.mgt; peer-reviewed